Heat Shock Strengthens the Protective Potential of MSCs in Liver Injury by Promoting EV Release Through Upregulated Autophagosome Formation - Wang, Tingting; Gong, Yihang; Lin, Huizhu; Li, Xuejiao; Liang, Jinliang; Yuan, Xiaofeng; Li, Cuiping; Hu, Zhongying; Chen, Haitian; Xiao, Jiaqi; Zhang, Jiebin; Liu, Yasong; et al. (Journal of extracellular vesicles, 2025)
ABSTRACT Mesenchymal stem cell‐derived extracellular vesicles (MSC‐EVs) show powerful potential in the treatment of multiple diseases. However, the low yield of MSC‐EVs severely restricts their clinical application. Here, heat shock (HS), a moderate external stimulus, can enhance EVs release of MSCs by upregulating autophagosome formation. Mechanistically, HS elevates TRPV2 expression to induce Ca2+ influx and then promotes the activity of two succinylases, SUCLG2 and OXCT1, followed by increasing the succinylation of YWHAZ (a 14‐3‐3 protein) at lysine 11 (K11). Acting as an adaptor protein, YWHAZ's succinylation at K11 inhibits its degradation, reinforcing YWHAZ‐ULK1 binding, which upregulates ULK1 S555 phosphorylation to promote autophagosome formation and enhance EV release of MSCs. Additionally, the improved therapeutic efficacy of HS‐treated MSCs via EV release has been shown in two liver injury models—hepatic ischemia/reperfusion injury (HIRI) and acetaminophen‐induced liver injury. These findings proved that HS, an easily implementable and cost‐effective method, can be used to elevate MSC‐EV yield in mass production.